Lactobacillus paracasei feeding improves the control of secondary experimental meningococcal infection in flu-infected mice - Belkacem, Nouria (BMC Infect Dis, 2018)
BACKGROUND: The use of probiotics to improve anti-microbial defence, such as for influenza infections, is increasingly recommended. However, no data are available on the effect of probiotics on flu-associated secondary bacterial infections. There is strong evidence of a spatiotemporal association between influenza virus infection and invasive Neisseria meningitidis. We thus investigated the effect of feeding mice Lactobacillus paracasei CNCM I-1518 in a mouse model of sequential influenza-meningococcal infection. METHODS: We intranasally infected BALB/c mice with a strain of influenza A virus (IAV) H3N2 that was first adapted to mice. Seven days later, a secondary bacterial infection was induced by intranasal administration of bioluminescent N. meningitidis. During the experiment, mice orally received either L. paracasei CNCM I-1518 or PBS as a control. The effect of L. paracasei administration on secondary bacterial infection by N. meningitidis was evaluated. RESULTS: Oral consumption of L. paracasei CNCM I-1518 reduced the weight loss of infected mice and lowered the bioluminescent signal of infecting meningococci. This improvement was associated with higher recruitment of inflammatory myeloid cells, such as interstitial monocytes and dendritic cells, to the lungs. CONCLUSIONS: Our data highlight the role of the gut-lung axis. L. paracasei CNCM I-1518 may boost the defence against IAV infection and secondary bacterial infection, which should be further studied and validated in clinical trials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-018-3086-9) contains supplementary material, which is available to authorized users.